Structural and chemical changes in hardwood cell walls during early stages of flash pyrolysis - Lindstrom, Jake K.; Peterson, Chad A.; Ciesielski, Peter N.; Ralph, John; Chen, Mingjie; Jakes, Joseph E.; Johnston, Patrick A.; Rollag, Sean A.; Brown, Robert C. (Frontiers in Energy Research, 2024)
Volatile products from thermal decomposition of lignocellulosic biomass have been well characterized, but the solid- and liquid-phase reactions during the early stages of decomposition are largely unknown. Here the initial solid-phase biomass thermal deconstruction reactions were analyzed in situ and with high particle heating rates, delineating how these processes occur. A variety of instrumentation was used to quantify the extent and relative rates of deconstruction, demonstrating that biopolymers resist the thermally energetic conditions to differing degrees, even when ensconced in biomass cell walls. Hemicellulose and the more frangible lignin components decompose and volatilize more readily than cellulose, which temporarily enriches biomass with cellulose. These chemical changes manifest in larger cell wall structural and mechanical property transformations. In all, this investigation concludes that these solid-phase reactions strongly influence the production rates of volatile species and will require additional study before these processes can be modeled precisely to improve yields of desired product.